2021
DOI: 10.1002/chem.202003931
|View full text |Cite
|
Sign up to set email alerts
|

A Local D4h Symmetric Dysprosium(III) Single‐Molecule Magnet with an Energy Barrier Exceeding 2000 K**

Abstract: Three six‐coordinate DyIII single‐molecule magnets (SMMs) [Dy(OtBu)2(L)4]+ with local D4h symmetry are obtained by optimizing the equatorial ligands. One of the compounds with L=4‐phenylpyridine shows an energy barrier (Ueff) of 2075(11) K, which is the third largest Ueff, and the first Ueff>2000 K for SMMs with axial‐type symmetry so far. Ab initio analysis indicates that the exceptional uniaxial magnetic anisotropy is deeply related to the axially compressed octahedral geometry. This work provides a new insi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 65 publications
4
63
0
Order By: Relevance
“…Complex 6.1 [41] has one of the shortestD y ÀOd istances,aDy-O-Dy angle of 1808 and four weak equatorial donors; to date, this complex shows the highest U eff value as well as the biggest GS-ES 1 energy gapf or any Ln alkoxide or aryloxide SMM. However,h aving ah igh energy barrier is not the sole requirement to provide improved SMMs, and this is when the effects of co-ligands can help.…”
Section: Effect Of Co-ligandsmentioning
confidence: 94%
See 4 more Smart Citations
“…Complex 6.1 [41] has one of the shortestD y ÀOd istances,aDy-O-Dy angle of 1808 and four weak equatorial donors; to date, this complex shows the highest U eff value as well as the biggest GS-ES 1 energy gapf or any Ln alkoxide or aryloxide SMM. However,h aving ah igh energy barrier is not the sole requirement to provide improved SMMs, and this is when the effects of co-ligands can help.…”
Section: Effect Of Co-ligandsmentioning
confidence: 94%
“…Ideal axially elongated-Oh, PB and HB geometries would generate D 4h , D 5h and D 6h local symmetries, respectively. [13,17,41] If these ideal local symmetries can be achieved they can create highly axial ligand fields and increase U eff by restricting some degrees of freedom responsible for generating the transverse CF (eliminating B q6 ¼0 k terms) thereby suppressing QTM. [13,17,35,41] Unfortunately no molecules have been reported that have such ideal symmetry,and indeed strictly D 5h symmetry cannot be found in acrystalline material.…”
Section: Overviewmentioning
confidence: 99%
See 3 more Smart Citations